Automatic anatomical foot and ankle coordinate toolbox - Peterson, Andrew C.; Kruger, Karen M.; Lenz, Amy L. (Frontiers in Bioengineering and Biotechnology, 2023)
Accurate analysis of bone position and orientation in foot and ankle studies relies on anatomical coordinate systems (ACS). Reliable ACSs are necessary for many biomechanical and clinical studies, especially those including weightbearing computed tomography and biplane fluoroscopy. Existing ACS approaches suffer from limitations such as manual input, oversimplifications, or non-physiological methods. To address these shortcomings, we introduce the Automatic Anatomical Foot and Ankle Coordinate Toolbox (AAFACT), a MATLAB-based toolbox that automates the calculation of ACSs for the major fourteen foot and ankle bones. In this manuscript, we present the development and evaluation of AAFACT, aiming to provide a standardized coordinate system toolbox for foot and ankle studies. The AAFACT was evaluated using a dataset of fifty-six models from seven pathological groups: asymptomatic, osteoarthritis, pilon fracture, progressive collapsing foot deformity, clubfoot, Charcot Marie Tooth, and cavovarus. Three analyses were conducted to assess the reliability of AAFACT. Firstly, ACSs were compared between automatically and manually segmented bone models to assess consistency. Secondly, ACSs were compared between individual bones and group mean bones to assess within-population precision. Lastly, ACSs were compared between the overall mean bone and group mean bones to assess the overall accuracy of anatomical representation. Statistical analyses, including statistical shape modeling, were performed to evaluate the reliability, accuracy, and precision of AAFACT. The comparison between automatically and manually segmented bone models showed consistency between the calculated ACSs. Additionally, the comparison between individual bones and group mean bones, as well as the comparison between the overall mean bone and group mean bones, revealed accurate and precise ACSs calculations. The AAFACT offers a practical and reliable solution for foot and ankle studies in clinical and engineering settings. It accommodates various foot and ankle pathologies while accounting for bone morphology and orientation. The automated calculation of ACSs eliminates the limitations associated with manual input and non-physiological methods. The evaluation results demonstrate the robustness and consistency of AAFACT, making it a valuable tool for researchers and clinicians. The standardized coordinate system provided by AAFACT enhances comparability between studies and facilitates advancements in foot and ankle research.